Interactive effects of motor coordination and socioeconomic status on fundamental motor skills - Difi Deofsila; Syahrial Bakhtiar; Gusril Gusril; Yendrizal Yendrizal; Lucy Pratama Putri; Risky Syahputra (Global Econedu, 2026)
This study aimed to examine the individual and combined effects of motor coordination and socioeconomic status on Fundamental Motor Skills (FMS) among elementary school students. A quantitative study using a 2 × 2 factorial design was conducted involving 72 students selected through purposive sampling from a population of 101 students at SDN 45 Bungo Pasang, Padang City. FMS were assessed using the Test of Gross Motor Development-2 (TGMD-2), motor coordination was measured using the (KTK), and socioeconomic status was classified based on parental socioeconomic data. Data were analyzed using descriptive statistics and Two-Way ANOVA. Significant differences were found between students with high and low motor coordination (p = 0.028) and between students with moderate and low socioeconomic status (p = 0.014). A significant interaction effect was also identified between motor coordination and socioeconomic status (p < 0.001). FMS development is influenced by both motor coordination and socioeconomic conditions, highlighting the importance of integrating individual motor competence and environmental support in physical education programs.